2016
DOI: 10.1007/s10266-016-0234-9
|View full text |Cite
|
Sign up to set email alerts
|

Color stability of recent composite resins

Abstract: The objective of the study was to evaluate the color stability of 8 recently developed resin composites when exposed to various staining agents. Six disc-shaped specimens made out of 8 resin composite materials were immersed in artificial saliva, coffee, coke, tea, orange juice and red wine. The initial color (T0) of the 288 specimens was assessed by a calibrated reflectance spectrophotometer (SpectroShade, MHT) over a black as well as a white background. All specimens were kept in an incubator (INP-500, Memme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
90
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(109 citation statements)
references
References 42 publications
(41 reference statements)
6
90
0
5
Order By: Relevance
“…The low pH of 4.5 of the red wine used in this study and its relatively high level of tannins may serve as an explanation for its high staining capacity, especially if compared to the coffee brewed in "lungo" mode. These results are in line with the precedent study done on unpolished samples [40]. It is of interest to underline the quite high staining potential of curry only when mixed with water.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The low pH of 4.5 of the red wine used in this study and its relatively high level of tannins may serve as an explanation for its high staining capacity, especially if compared to the coffee brewed in "lungo" mode. These results are in line with the precedent study done on unpolished samples [40]. It is of interest to underline the quite high staining potential of curry only when mixed with water.…”
Section: Discussionsupporting
confidence: 90%
“…We even decided to mix it alternatively with water or oil (according to different food recipes) in order to see if some differences could be seen. On the other hand, we maintained, according to previous studies [40,51] arti icial saliva (Glandosan®, Helvepharm AG, Frauenfeld, Switzerland) as a control.…”
Section: Discussionmentioning
confidence: 99%
“…This degradation effect of alcohol on the composite resin lead to rough surfaces that absorb colorant pigments . Moreover, with regard to color changes in red wine, Ardu et al emphasized its relative acidity (pH = 4.5) and tannin content. Similar to red wine, coffee caused a significant color change on all restorative materials even in the first 24 h. Previous reports showed that coffee is one of the most colorant beverages for the composite resins .…”
Section: Discussionmentioning
confidence: 99%
“…5,6 There is no unanimity about the incidence of failures that lead to replacing the composites, however, today the main cause of changing resins, direct or indirect indication, is the change in color. As a result and because of the aesthetic excellence sought by patients, composite manufacturers continuously seek to improve the optical properties of these materials to enable the adequate reproduction of natural teeth characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…1 The composites have become the dentists' materials of choice for most restorations, due to their sophisticated aesthetic characteristics in the anterior region and due to their adequate biomechanical strength when used in posterior teeth. [2][3][4][5] Choosing an esthetic restorative material is largely due to its ability to imitate the color of the dental element. 6 Using it as a model for obtaining the optical characteristics of dentin and enamel is based on the concept of natural stratification, a simple and effective approach to manufacture highly aesthetic direct restorations.…”
Section: Introductionmentioning
confidence: 99%